Los factores de riesgo psicosocial y su incidencia en la salud laboral de los trabajadores de la empresa Ecuandros Ecuadorian New Roses S.A. Durante el año 2013. - León Flores, Sonia de los Angeles (2015)
This thesis project tries to highlight the impact of the psychosocial factors in the floricola field, which have been less assessed because of its subjective character but they potentially affect of an important way in the development of processes and activities. The threat to assess the psychosocial risks is due to the range of concepts which show up according to the characteristics of the workers and employees´ organizations who help them, that´s why it´s important to do an analysis and classification of psychosocial risks, as well to check the different existing methods to evaluate them (chapter II) for this reason Navarra method was chosen to its application since it sums up the intervention process changing into clearer and acceptable to the factory, generating a synthetic and organized document which contains and visualize all the information that authorities and security officers can lead of a comprehensible way (chapter III). After doing the diagnostic process and with the required information to determine the source of risks, it will be presented the proposal to improve it (chapter IV), in which the general leadership can take necessary changes to comply the current legislation, improving its economic and productive indicators, but the most important to look after the workers and employees’ health.